Digital Transformation and Operational Efficiency: A Two-Stage DEA Approach in Electricity Distribution Units in Central Java and the Special Region of Yogyakarta - Singgih Budiaji; Lilik Sugiharti (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines the impact of digital transformation, facilitated by the PLN Mobile application, on the operational efficiency of Customer Service Units (UP3) under PT PLN (Persero) Distribution Main Unit (UID) Central Java and the Special Region of Yogyakarta. The Digital Transformation Index (DTI) is constructed using the ratio of PLN Mobile users to total customers and the ratio of digital complaints to total complaints. The analysis covers 78 Decision Making Units (DMUs) over the period 2020–2025. Technical efficiency is measured using input-oriented Data Envelopment Analysis (DEA) under both Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) assumptions. A two-limit Tobit regression model is subsequently employed to examine the determinants of efficiency. The results indicate average efficiency scores of 0.755 (CRS) and 0.791 (VRS). The number of customers significantly reduces efficiency, while the Capacity Index shows a positive relationship at the 10% significance level. In contrast, the Digital Transformation Index (DTI) does not demonstrate statistical significance. The findings suggest that operational capacity and service load pressures play a more substantial role in explaining efficiency variations than the intensity of front-end digitalization.